2002
DOI: 10.1182/blood-2002-01-0265
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of T-cell responses to Aspergillus fumigatus antigens in healthy individuals and patients with hematologic malignancies

Abstract: Invasive aspergillosis has become a major cause of infection-related mortality in nonneutropenic patients after allogeneic stem cell transplantation (SCT). To assess the potential role of Aspergillusspecific T-cell responses for the successful control of invasive aspergillosis, lymphoproliferative responses to Aspergillus fumigatus antigens were studied in healthy individuals, patients with evidence of invasive aspergillosis, and patients late after allogeneic SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
193
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(208 citation statements)
references
References 34 publications
8
193
0
7
Order By: Relevance
“…4,16 Importantly, several extracts prepared under identical conditions resulted in comparable numbers and function of the generated cells, indicating the reproducibility of our system (data not shown). In addition, extensive controls after stimulation, isolation and culture of anti-Aspergillus T cells did not reveal contamination with a pathogen or endotoxin.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…4,16 Importantly, several extracts prepared under identical conditions resulted in comparable numbers and function of the generated cells, indicating the reproducibility of our system (data not shown). In addition, extensive controls after stimulation, isolation and culture of anti-Aspergillus T cells did not reveal contamination with a pathogen or endotoxin.…”
Section: Discussionmentioning
confidence: 73%
“…3 Conversely, patients surviving aspergillosis show significant antigen-specific proliferation of IFN-g producing T cells, supporting the crucial role of a T-helper (T H ) 1 reactivity in the control of infection. 4 Over the past decade, significant progress has been made in reconstituting adoptive cell immunity in hematopoietic transplant patients with ex vivo generated antigen-specific T cells to restore essential responses for protection against a specific pathogen. For example, eight transplant recipients who lacked CMVspecific T-cell immunity and did not respond to antiviral chemotherapy for CMV disease, received 1 Â 10 7 CMVspecific T cells per m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Data from our group have also demonstrated that isolated gamma-delta T cells can mediate anti-aspergillus activity. 11 Gamma-delta T lymphocytes can be highly enriched for under good manufacturing practice conditions using the Clinimacs device 16,17 and also easily be activated and expanded in vivo by stimulation with aminobisphosphonates. 18 Thus, this cell population that also mediates antiviral and antitumor activity, 19,20 but does not mediate alloreactivity will be a very attractive option to be used for adoptive immunotherapy for infection and tumor control post transplant.…”
Section: Immunotherapy For Fungal Infectionsmentioning
confidence: 99%
“…Patients undergoing allo-SCT are also at a high risk to develop invasive aspergillosis and we have shown that a low rate of T-cell proliferation when exposed to aspergillus antigens as well as a predominant aspergillus-specific Th2 response are associated with a worse outcome of invasive aspergillosis in patients who have undergone allo-SCT. 11 Several groups have established methods to select and expand aspergillus-specific T cells and a small clinical trial has shown promising activity and good safety of the transfer of in vitro stimulated and selected aspergillus-specific T-cell clones to patients with uncontrolled invasive aspergillosis following allo-SCT. 12 In addition, we and others have shown that also activated natural killer cells-which can be easily selected and enriched for-can mediate anti-aspergillus activity.…”
Section: Immunotherapy For Fungal Infectionsmentioning
confidence: 99%
“…The Th2 subset of CD4+ T cells secretes IL-4, IL-6, and IL-10 cytokines and is responsible for the stimulation of humoral immune response, through which it helps B cell activation [7]. It is considered that Th1 type cytokine responses are associated with strong immune responses and resistance to lethal fungal infections, while Th2 type cytokine responses correlate with minimum cell-mediated immune responses and the increase of antibody production [8].…”
Section: Introductionmentioning
confidence: 99%